Two new species of stoneflies in the Leuctra ferruginea group (Plecoptera: Leuctridae), with notes on the Leuctra species known for Mississippi and Alabama, U.S.A. - Harrison, Audrey B. (Illiesia, 2010)
Leuctra colemanorum sp.n. and L. hicksi sp.n. are proposed from Mississippi specimens and compared to related members of the L. ferruginea (Walker) complex. Leuctra colemanorum is placed in the L. ferruginea subgroup and L. hicksi is placed in the L. rickeri James subgroup. Comparative SEM images are provided for L. alabama James, L. ferruginea, L. paleo Poulton & Stewart, L. rickeri and L. szczytkoi Stark & Stewart, and updates are provided for the Leuctra species lists for Mississippi and Alabama. The first records of L. triloba Claassen from Alabama, L. ferruginea for Louisiana and Tennessee, and L. carolinensis Claassen for Mississippi are presented. Potential synonymies of L. rickeri with L. alabama and L. paleo with L. szczytkoi are suggested.
Keywords: entomology; Leuctra ferruginea; Leuctridae; new species; Plecoptera; Mississippi; U.S.A.; Alabama